Gap Analysis of Public Perceptions and Expectations on Service Quality of the Women and Children Protection Unit (PPA) at the Criminal Investigation Division of Cirebon City Police Using the SERVQUAL Approach - Agustinus Ronald Tri Cahya Waine; Oscarius Yudhi Ari Wijaya; Novi Indah Erlyanti; Elvianus Laoli (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The Women and Children Protection Unit (PPA) of Polresta Cirebon faces a high number of cases of violence against women and children, requiring responsive, empathetic, and professional services. This study aims to analyze the gap between public perception and expectation of PPA service quality using the SERVQUAL approach as a basis for evaluation and service improvement. This research employs SERVQUAL theory, the concepts of public perception and expectation, principles of women and child protection, and police transformation. The study uses a quantitative approach with a survey method through questionnaires to measure public perception and expectation of the PPA Unit services at Sat Reskrim Polresta Cirebon based on five SERVQUAL dimensions, then analyzed using gap analysis and quadrant mapping to determine service improvement priorities. The research findings are as follows: 1) Public perception of PPA services: Tangibles 3.12; Reliability 2.90; Responsiveness 2.96; Assurance 2.97; Empathy 3.06, indicating services are fairly good but not yet optimal; 2) Public expectation of services: Tangibles 4.55; Reliability 4.55; Responsiveness 4.58; Assurance 4.62; Empathy 4.63, indicating very high public expectations; 3) Gap between perception and expectation: Tangibles -1.43; Reliability -1.65; Responsiveness -1.62; Assurance -1.65; Empathy -1.57, showing service quality is below expectations; 4) Dimensions with the largest gaps are Reliability -1.65 and Assurance -1.65, with improvement priorities on service consistency, procedural clarity, professionalism, and safety; 5) All dimensions have negative gaps, with improvement priorities on reliability, assurance, and empathy, while aspects such as responsiveness, procedural clarity, and professionalism need to be maintained. The study concludes that the service quality of the PPA Unit at Satreskrim Polresta Cirebon is fairly good but still below expectations, with the largest gaps in reliability and assurance, requiring priority improvements in consistency, professionalism, safety, and staff empathy